Navigating the tension between city branding and authenticity: a conceptual framework - Eko Nursanty; Rahmawaty Abu Hassan; Made Ika Prastyadewi (Institute for Advanced Science Social, and Sustainable Future, 2023)
As cities around the world increasingly embrace branding as a means of promoting economic growth and attracting investment, there has been a growing tension between the desire to create a strong and recognizable city brand and the need to maintain a sense of authenticity and place identity. This paper presents a conceptual framework for understanding this tension and proposes strategies for navigating it in the context of city branding. Drawing on existing literature and case studies of successful and unsuccessful city branding campaigns, the framework highlights the importance of balancing the desire for a strong city brand with the need to preserve a sense of authenticity and place identity. The framework suggests that city branding campaigns should be designed with careful consideration of local history, culture, and values, and should engage a diverse range of stakeholders in the branding process. Ultimately, the paper argues that successful city branding campaigns must strike a delicate balance between the desire for a strong and recognizable brand and the need to maintain a sense of authenticity and place identity.